Application of nanotechnology in air purifiers as a viable approach to protect against Corona virus - Ali Mahmoudi; Seyedeh Belin Tavakoly Sany; Marzieh Ahari Salmasi; Ali Bakhshi; Arad Bustan; Sahar heydari; Majid Rezayi; Fatemeh Gheybi (IET Nanobiotechnology)
Abstract The outbreak of COVID‐19 disease, the cause of severe acute respiratory syndrome, is considered a worldwide public health concern. Although studies indicated that the virus could spread through respiratory particles or droplets in close contact, current research have revealed that the virus stays viable in aerosols for several hours. Numerous investigations have highlighted the protective role of air purifiers in the management of COVID‐19 transmission, however, there are still some doubts regarding the efficiency and safety of these technologies. According to those observations, using a proper ventilation system can extensively decrease the spread of COVID‐19. However, most of those strategies are currently in the experimental stages. This review aimed at summarising the safety and effectiveness of the recent approaches in this field including using nanofibres that prevent the spread of airborne viruses like SARS‐CoV‐2. Here, the efficacy of controlling COVID‐19 by means of combining multiple strategies is comprehensively discussed.